Analisis Komunikasi Antar Budaya dalam Film Bumi Manusia - Joni Helandri (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2021)
This research focuses on the intercultural communication contained in the film Bumi Manusia. In the discussion, several problem formulations were compiled, namely: (1) what are the elements of intercultural communication in the film Bumi Manusia? (2) What are the forms of intercultural communication media in the film Bumi Manusia? And (3) What are the elements of sociology of communication in the film Bumi Manusia? The purpose of this study is to determine the elements of intercultural communication, and to know the sociological elements of communication in the film Bumi Manusia. This research is a type of library research (library research) using a qualitative descriptive approach, by analyzing the contents of the film Bumi Manusia, this unit of analysis in the form of fragments of images, text, sounds, or sounds contained in the film Bumi Manusia.